Serotonin-1A receptors in major depression quantified using PET: Controversies, confounds, and recommendations - Shrestha, Saurav; Hirvonen, Jussi; Hines, Christina S.; Henter, Ioline D.; Svenningsson, Per; Pike, Victor W.; Innis, Robert B. (NeuroImage (Orlando, Fla.), 2012)
The serotonin-1A (5-HT1A) receptor is of particular interest in human positron emission tomography (PET) studies of major depressive disorder (MDD). Of the eight studies investigating this issue in the brains of patients with MDD, four reported decreased 5-HT1A receptor density, two reported no change, and two reported increased 5-HT1A receptor density. While clinical heterogeneity may have contributed to these differing results, methodological factors by themselves could also explain the discrepancies. This review highlights several of these factors, including the use of the cerebellum as a reference region and the imprecision of measuring the concentration of parent radioligand in arterial plasma, the method otherwise considered to be the ‘gold standard’. Other potential confounds also exist that could restrict or unexpectedly affect the interpretation of results. For example, the radioligand may be a substrate for an efflux transporter – like P-gp – at the blood–brain barrier; furthermore, the binding of the radioligand to the receptor in various stages of cellular trafficking is unknown. Efflux transport and cellular trafficking may also be differentially expressed in patients compared to healthy subjects. We believe that, taken together, the existing disparate findings do not reliably answer the question of whether 5-HT1A receptors are altered in MDD or in subgroups of patients with MDD. In addition, useful meta-analysis is precluded because only one of the imaging centers acquired all the data necessary to address these methodological concerns. We recommend that in the future, individual centers acquire more thorough data capable of addressing methodological concerns, and that multiple centers collaborate to meaningfully pool their data for meta-analysis. ► PET imaging of 5-HT1A receptor density in MDD patients has yielded mixed results. ► ‘Methodological’ rather than ‘clinical’ factors likely explain these discrepancies. ► One methodological confound is the use of the cerebellum as a reference region. ► Measuring parent radioligand concentrations in arterial plasma is imprecise. ► Other confounds are efflux transporter, radiometabolites, & 5-HT1A affinity states.